ANALISIS IMPLEMENTASI ASUHAN KEBIDANAN BERBASIS CONTINUITY OF CARE DI TPMB BIDAN DELIMA WINDA MAOLINDA KOTA BANJARMASIN - Wahdah, Rabia (Midwifery And Complementary Care, 2023)
ABSTRACT Background: Comprehensive midwifery care is comprehensive midwifery management care starting from pregnant women, giving birth, newborn babies (BBL) to family planning so that childbirth can take place safely and take place safely and babies are born safe and healthy until the postpartum period. Objective:. Able to provide continuity of care midwifery care to Mrs. D at TPMB Winda Maolinda Methods: A cross-sectional study was facility-based (retrospective analysis) and used simple randomsampling (SRS). Result: This research was conducted at the PMB Delima Winda Maolinda clinic in 2022 with an analysis of the implementation of continuity of care-based midwifery care at TPMB Bidan Delima Winda Maolinda, Banjarmasin City.Conclusion: The implementation of continuity of care-based midwifery care at TPMB Bidan Delima Winda Maolinda, Banjarmasin City has been carried out comprehensively and continuously. Keywords: Implementation, Midwifery care, COC